The intervention in the autism spectrum disorder in the alterations in intersubjectivity and the theory of the mind - Calderón Coronado, Raquel (2019)
Knowing about the autism spectrum disorder (ASD) and its multiple characteristics lead us to internalize terms such as intersubjectivity, the Theory of Mind (ToM), symbolic play, joint attention, empathy; with the purpose of improving the intervention process and its interpersonal relationships. The conceptual aspects, definition and description of these competences will lead us to a better development of language and their interpersonal relationships with their peers. The objective of this study is to update the knowledge about ASD and how the alterations of intersubjectivity and ASD are manifested in it. On the other hand, it is important that every educator who interacts with children with ASD, knows what is the process of intersubjectivity, the TOM, the symbolic game and its incidence in the development of language and the child’s relationships with ASD. It is important to consider that difficulties in the area of communication and language are also characteristic of ASD and as teachers, specialists and therapists we cannot stop analyzing and researching them, since they can manifest themselves to a greater or lesser extent, with more or less intensity, but in both cases they require proper intervention and management. We must not forget that people with ASD present failures in the area of communication, not only in language, an essential vehicle of communication, but also in their own communicative intention; therefore, it is important to work and intervene in this area, since it is the one that gives rise to other areas of development such as: socialization, interaction with others and, therefore, a better development in the school and its community.